2019
DOI: 10.15244/pjoes/99302
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Framework of Provincial Carbon Emission Peak Prediction in China: An Empirical Analysis of Hebei Province

Abstract: Greenhouse gas emission reduction has become the focus of today's research. In December 2009 the Chinese government proposed targets aimed at controlling greenhouse gas emissions. More specifically, it was decided that CO 2 emissions per unit gross domestic product (GDP) in China should be cut by 40-45% in 2020 compared to 2005. Then China and the United States jointly issued the "China-U.S. Joint Presidential Statement on Climate Change" in November 2014 [1], and China claimed to peak CO 2 emissions around 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This paper constructs a model of the effect of the TDI on the ERI from the classical STIRPAT environmental impact model, which has the following standard form [77][78][79]: The HH-type represents neighborhoods where both the TDI and ERI have high values and symbiotically promote each other's development. This type is primarily concentrated in Shanghai, Zhejiang, and southern Jiangsu regions.…”
Section: Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper constructs a model of the effect of the TDI on the ERI from the classical STIRPAT environmental impact model, which has the following standard form [77][78][79]: The HH-type represents neighborhoods where both the TDI and ERI have high values and symbiotically promote each other's development. This type is primarily concentrated in Shanghai, Zhejiang, and southern Jiangsu regions.…”
Section: Model Constructionmentioning
confidence: 99%
“…This paper constructs a model of the effect of the TDI on the ERI from the classical STIRPAT environmental impact model, which has the following standard form [77][78][79]:…”
Section: The Effect Of the Tdi On The Eri 431 Model Constructionmentioning
confidence: 99%
“…Zhang L et al applied the tabu search (TS) algorithm to the least squares support vector machine (LSSVM) optimized by the particle swarm optimization (PSO) algorithm to predict the carbon emissions of China's energy consumption, and finally found that its carbon emissions will gradually decrease around 2026 (Zhang et al 2019). STIRPAT model is more accurate in predicting the trend of carbon emission changes, while GA-BP model is more accurate in predicting the numerical value (Li &Du 2019). This result also shows the necessity of exploring the change of transmission mechanism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of study regions, the existing literature on CO2 emission projections in China is mainly focused on the national (Fan et al, 2022 ; Jiang et al, 2019 ; Li, 2020 ), multi-province (Fang et al, 2019 ; Zhang et al, 2021 ; Zuo et al, 2020 ), and single-province (Li & Du, 2019 ; Li et al, 2021 ; Ren & Long, 2021 ), and less literature is available on CO2 emission projections from the perspective of metropolitan areas. The only literature that exists is only at the scale of a single metropolitan area (Guo et al, 2018b ; Liu et al, 2022 ), and there is a gap in the literature on CO2 emission projections for Chinese metropolitan areas at the national level.…”
Section: Introductionmentioning
confidence: 99%